Analysis of Agression Level of Junior Karate Athlete on Kumite Number - Dewi Putri Susanti; Samsul Bahri; Giri Prayogo (Universitas PGRI Palembang, 2023)
In sports, aggression is needed to be able to control the match and scored a victory. Aggressive behavior is one aspect of psychology that is closely related to martial arts sports, especially in karate. The aggressiveness needed by athletes is in the form of aggression aimed at winning the match without harming the opponent. So that aggressiveness in karate sports, especially in kumite numbers, is indeed an inherent characteristic because the matches carried out use physical contact as a whole. This study aims to determine how much the level of aggressiveness of junior karate athletes, especially in kumite numbers. This type of research is quantitative descriptive research using a questionnaire given to a sample of (N = 15) athletes. In this study, the results obtained a very high level of aggressiveness as much as 1 (7%), a high level of aggressiveness as much as 2 (13%), a moderate level of aggressiveness as much as 11 (73%), and a low level of aggressiveness as much as 1 (7%). This can be interpreted that the level of aggressiveness of junior karate athletes in kumite numbers uses aspects of aggressiveness as a way to win matches.